A dimensão sociopolítica do documentário Dia de festa, de Toni Venturi - Souza, Claudia de (2015)
The present dissertation has as its main focus, the relation between cinema and social reality and as its object of study the documentary production and its relation to the Brazilian society; since the perception of such genre is related to other relevant questions and social problems. The documentary Dia de festa (2006), directed by Toni Venturi, was chosen to be the empiric constraint of the main study proposal in order to raise the hypothesis that considers documentary production to be responsible for the critique discourse development and social problems. Under those cited considerations, it has been attempted through the narrative and politic structure observed in this documentary, the elements that compound its cinematographic discourse and its technical options as well as its aesthetic revealed. The methodology of this research was based on the bibliographic reference, the interview with the film director Toni Venturi, the reference from other documentaries that approach the social problems in an attempt to narrow the relation between the researched theoretical production and the structure of the film. Under this methodology and the objective of confirming the given hypothesis, it was necessary a brief exposure of the origin and the history of documentaries until the beginning of the Direct Cinema and Cinema Truth (Labaki, Catelli, Weller e Nichols), which reverberated in the Brazilian documentary production, specially between 1960 and 1990 (Lins e Mesquita, Labaki, Lins, Xavier, Bernardet e Eduardo); it was also necessary to point out the peculiarities in the genre from the 1990s by contextualizing the mediatic society, in which some productions and triggers stand out (Lins, Bentes, Lins e Mesquita) and look into part of the elements that constitute its structure, language and discourse (Nichols e Puccini), placing it into the context of the contemporary audiovisual production and its methodological importance through social sciences (Ibiapina) and on the relation between art and society